Pharmaceutical and Biomedical Project Management in a Changing Global Environment - Babler, Scott D; Ekins, Sean (Wiley series on technologies for the pharmaceutical industry, 2010)
Pharmaceutical and Biomedical Portfolio Management in a Changing Global Environmentexplores some of the critical forces at work today in the complex endeavour of pharmaceutical and medical product development.  Written by experienced professionals, and including real-world approaches and best practice examples, this new title addresses three key areas – small molecules, large molecules, and medical devices - and provides hard-to-find, consolidated information relevant to and needed by pharmaceutical, biotech, and medical device company managers.